The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/sltb.12288
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Longitudinal Direct and Indirect Effects of Attitudes, Self‐Efficacy, and Behavioral Intentions on Practice Behavior Outcomes of Suicide Intervention Training

Abstract: The purpose of this study was to use a longitudinal path analysis to test attitudes toward suicide prevention, self-efficacy, and behavioral intentions as mediators/moderators of clinical skill development over time following suicide intervention training. Results support a direct effect of attitudes on practice behaviors and self-efficacy, but no moderating effect. Self-efficacy performed as a mediator of practice behaviors over time. Behavioral intention had a direct effect on practice behaviors and mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
(56 reference statements)
7
14
1
Order By: Relevance
“…As hypothesized, behavioral health providers who reported being more confidence in their skills related to suicide care were also more likely to incorporate best practices. This result is in accordance with previous research that suggests that level of comfort and self‐efficacy beliefs associated with working with suicidal people are related to greater use of evidenced‐based practices, even when controlling for individual differences and case load (Lee, Osteen, & Frey, ; Osteen, Frey, Woods, Ko, & Shipe, ; Roush et al., ). In fact, one previous study found that providers with higher comfort levels, regardless of fear of negative outcomes, were more likely to adequately implement suicide risk assessments (Roush et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesized, behavioral health providers who reported being more confidence in their skills related to suicide care were also more likely to incorporate best practices. This result is in accordance with previous research that suggests that level of comfort and self‐efficacy beliefs associated with working with suicidal people are related to greater use of evidenced‐based practices, even when controlling for individual differences and case load (Lee, Osteen, & Frey, ; Osteen, Frey, Woods, Ko, & Shipe, ; Roush et al., ). In fact, one previous study found that providers with higher comfort levels, regardless of fear of negative outcomes, were more likely to adequately implement suicide risk assessments (Roush et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…At last, it will be important to develop studies exploring whether some modalities of training (e.g., experiential training versus online training) are associated with higher confidence and implementation of practices among behavioral health providers (Roush et al., ; Silva et al., ). For instance, previous research has suggested that although most trainings might produce changes in knowledge and attitudes, it is through active learning strategies that behavioral changes are produced (Beidas & Kendall, ; Osteen et al., ). In sum, our results underscore the importance of examining packages of trainings for suicide prevention and of establishing if there is incremental utility of delivering multiple trainings to increase levels of confidence and practice among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Practice skills were not tested directly, but improvement in self-efficacy is still important, since a sense of confidence is critical for motivation and performance (Bandura 2001;Bandura & Locke, 2003). Self-efficacy, "the belief in one's capabilities to organize and execute specific courses of action" (Ozer et al, 2004, p. 102), has been studied as a key factor linked to subsequent behavior and application of practice skills (Kunst, Mitchell, & Johnson, 2017;Lippke, Wiedemann, Ziegelmann, Reuter, & Schwarzer, 2009;Osteen, Frey, Woods, Ko, & Shipe, 2016) The online training successfully improved service providers' knowledge relevant to effective practice with youth and young adults with mental health needs. Although knowledge scores improved significantly for both sets of service providers, group membership was shown to be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers may report the impact of training on practice behaviors, attitudes, self-efficacy, and knowledge for each individual construct without regard to the interaction of these multiple factors. Research is available that explores the potential moderating roles of baseline characteristics such as professional role and experience on the intervention behaviors with evidence supporting the notion that the development of intervention behaviors is impacted by more than just the training in and of itself (Osteen, Frey, Woods, Ko, & Shipe, 2016;Tompkins, Witt, & Abraibesh, 2010). This approach has allowed the field to make statements about whether or not training is effective in improving these outcomes, but it has done little to explore the ''how/why'' question or to develop strong causal models linking these components.…”
Section: Core Training Constructsmentioning
confidence: 99%
“…Lee, Osteen, and Frey (2016) applied the SCT framework to a hierarchical analysis of change in clinical behaviors and found mixed support for the model; the results supported the role of self-efficacy in behavioral change but not for attitudes after controlling for individual and work-related characteristics. Osteen, Frey, Woods, Ko, and Shipe (2016) also used an SCT approach to analyze the direct and indirect effects of knowledge, attitudes, efficacy, and motivation of posttraining intervention behaviors and found strong evidence for the indirect effects of attitudes on self-efficacy and motivation and the indirect relationship of self-efficacy to posttraining intervention behaviors.…”
Section: Social Cognitive Theory (Sct)mentioning
confidence: 99%